A new synthesis of biologically active pyrroles: Formal synthesis of pentabromopseudilin, bimetopyrol, and several antitubercular agents. (22nd November 2019) - Karimi, Sasan; Ma, Shuai; Qu, Michelle; Chen, Biling; Ramig, Keith; Greer, Edyta M.; Szalda, David J.; Neary, Michelle C.; Berkowitz, William F.; Subramaniam, Gopal
Abstract: Although pyrroles have been synthesized from azido dienes, the corresponding reactions of structurally similar nitrodienes had not been investigated until it became the main focus of this study. This article describes the synthesis of several biologically active pyrroles and mechanistically intriguing results in connection with our new approach using nitrodienes in the presence of Ph3 P and a Mo catalyst, bis (acetylaceto)dioxomolybdenum (VI). The final precursor of pentabromopseudilin (PBP), pseudilin, was synthesized in four steps from o ‐hydroxycinnamaldehyde. An alternate pathway to PBP proceeded through o ‐methylpseudilin, prepared in two steps from o ‐methoxycinnamaldehyde. Both starting materials are commercially available. Similarly, bimetopyrol (2‐methyl‐4, 5‐bis( p ‐methoxyphenyl)pyrrole), a potent anti‐inflammatory, was prepared using the new methodology. The remarkable conversion of nitrodienes 14 and 15 to bimetopyrol highlights the formation of a nitroso or nitrene intermediate. We also established that 14 and 15 interconvert in the presence of ambient light and each converts to bimetopyrol when reacted separately. The wide application of our synthetic methodology includes preparation of several antitubercular and Herpes Simplex 2 (HSV2) agents. Abstract :